2018
DOI: 10.1007/s12035-018-1258-7
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist

Abstract: Oxidative stress is a key mediator of neuronal death in acute brain injuries, such as epilepsy, trauma, and stroke. Although it is accompanied by diverse cellular changes, increases in levels of intracellular zinc ion (Zn) and calcium ion (Ca) may play a critical causative role in oxidative neuronal death. However, the mechanistic link between Zn and Ca dyshomeostasis in neurons during oxidative stress is not well-understood. Here, we show that the exposure of cortical neurons to HO led to a zinc-triggered cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Intracellular Zn 2+ -dependent activation of TRPC5 channels was recently reported to contribute to oxidative neuronal death, 38 but the molecular mechanism of Zn 2+ regulation of TRPC5 was not identified. We have identified a putative intracellular zinc binding site of TRPC5, which is conserved in all TRPC channels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracellular Zn 2+ -dependent activation of TRPC5 channels was recently reported to contribute to oxidative neuronal death, 38 but the molecular mechanism of Zn 2+ regulation of TRPC5 was not identified. We have identified a putative intracellular zinc binding site of TRPC5, which is conserved in all TRPC channels.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may indicate that zinc is already bound in TRPC5:Pico145, or that the role of zinc in TRPC5 modulation is subtle, which is consistent with the delayed Zn 2+ -mediated [Ca 2+ ]i increase observed in calcium imaging experiments, and the small TRPC5 currents evoked by intracellular application of ZnCl2. 38 Part of the putative zinc binding site has also been implicated in TRPC5 glutathionylation: mutation of C176, C178 or C181 prevented TRPC5 opening in response to glutathionylation. 40 A separate report proposed that palmitoylation of C181 is required for correct trafficking of TRPC5 to the plasma membrane in striatal neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was demonstrated that zinc-treated cultured neurons produce ROS from their mitochondria [ 18 ] and trigger microglial activation [ 26 ]. In addition, previous studies by our group have observed that excessive zinc accumulation within brain hippocampal regions can lead to neurodegeneration after cerebral insult, such as ischemia [ 10 , 27 ], head trauma [ 25 ], hypoglycemia [ 28 ], and cultured neurons [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TRPC1/C4 and TRPC5 channels have been implicated in seizure-induced neuronal death in mouse lateral septum and hippocampus, respectively, in the pilocarpine-induced model of epilepsy ( Phelan et al, 2012 ). Inhibiting TRPC5 also protected neurons in pyriform cortex, amygdala, and hippocampus from death in kainate-treated rats with prolonged seizures ( Park et al, 2019 ) and in hippocampal CA3 neurons in a tramatic brain injury model ( Park et al, 2020 ). In these models, TRPC5 was thought to be activated by oxidation which first triggered a rise in cytosolic Zn 2+ levels and then opening of TRPC5 channels to mediate Ca 2+ influx, leading to neuronal cell death ( Park et al, 2019 ).…”
Section: The Role Of Trpcs In Neurodegenerative Diseases Aside From Smentioning
confidence: 99%